Tea with the Dames - Ein unvergesslicher Nachmittag - Michell, Roger; Bolter, Eben (KSM, 2019)
There are some films that deliver with such literal-minded generosity on the promise of their titles that all you can do in response is applaud, and in that respect - if no other - "Tea with the Dames" is the new "Snakes on a Plane". Roger Michell's documentary offers dames (a thespian quartet of them, comprising Judi Dench, Maggie Smith, Eileen Atkins and Joan Plowright) and tea and pretty much nothing else. Happily, that turns out to be enough for a wholly delightful talkathon, shot on location in the rambling country pile that Plowright once shared with Laurence Olivier. For the tea in question is not so much the beverage as a warm, steady stream of gossip, spilled lavishly, as four of the pre-eminent British actors of their generation reflect mirthfully on their careers, their lives and lovers, their ongoing insecurities and some 60 years of friendship between them. [variety.com]